(untitled) (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2023)
The problem in this study is the lack of youth athletes representing POPDA in Kab. Kampar due to the difficulty of teachers assessing youth athletes to take part in regional championships, especially basketball. The aim is to determine the validity of developing a web-based self-assessment application and to determine the reliability of the developed self-assessment application. This type of research is RnD using the ADDIE model. The subjects in this study were students of SMKN 1 Bangkinang Kota, taking samples by random sampling and the number of samples was 32 students. The data collection instrument used expert validation questionnaires, documentation, and basketball shooting tests. The data analysis technique used was the Aiken rater score analysis. The results of this study were that filling out a questionnaire by basketball experts obtained a value of 1,000 with a very valid category, measurement test experts obtained a value of 0.840 with a high category, material curriculum experts obtained a value of 0.932 in a high category and evaluation expert obtained a value of 0.932 in a high category with a reliability test result of 0.868 with reliable category. From the trial, it was found that 24 out of 32 students had succeeded in reaching the school KKM limit of 75. It can be concluded that the basketball shooting self-assessment application is valid and reliable and can be used as an assessment medium used by PJOK teachers in assessing students.